Strongly anisotropic spin and orbital Rashba effect at a tellurium - noble metal interface - Geldiyev, B.; Ünzelmann, M.; Eck, P.; Kißlinger, Tilman; Schusser, J.; Figgemeier, T.; Kagerer, P.; Tezak, N.; Krivenkov, M.; Varykhalov, A.; Fedorov, A.; Nicolaï, L.; et al. (Physical Review B, 2023)
We study the interplay of lattice, spin, and orbital degrees of freedom in a two-dimensional model system: a flat square lattice of Formula Presented atoms on a Formula Presented surface. The atomic structure of the Te monolayer is determined by scanning tunneling microscopy and quantitative low-energy electron diffraction. Using spin- and angle-resolved photoelectron spectroscopy and density functional theory, we observe a Te-Au interface state with highly anisotropic Rashba-type spin-orbit splitting at the Formula Presented point of the Brillouin zone. Based on a profound symmetry and tight-binding analysis, we show how in-plane square lattice symmetry and broken inversion symmetry at the Te-Au interface together enforce a remarkably anisotropic orbital Rashba effect which strongly modulates the spin splitting.
CRIS-Team Scopus Importer:2023-10-06